Valoración de rentas de capital con tipos de interés borrosos. - Ruiz Gracia, María Luisa; Sánchez Montero, Jesús María; Domínguez Serrano, María de los Ángeles (Cuadernos de Estudios Empresariales, 1992)
Sin resumen